JUMLAH KEPALA SEKOLAH DAN GURU DI SEKOLAH SWASTA MENURUT KELOMPOK UMUR PROVINSI BANTEN, SULAWESI UTARA, KALIMANTAN UTARA, DAN PAPUA SELATAN TAHUN 2023/2024 - Mutia Salsa Rizkyta; Nanda Zahira Shofa; Rizma Fauziah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This study discusses the distribution of the number of principals and teachers in private schools in Banten, North Sulaesi, North Kalimantan, and South Papua Provinces by age group. This research uses quantitative methods to analyze data from 2023/2024. The aim is to provide comprehensive information about the demographic gap among educators and to plan more effective education policies